Anti-static adhesive tape for electronic material and preparation method of anti-static adhesive tape

By regulating the ratio of crosslinking agent to antistatic agent in single-sided tape and designing an antistatic coating, the limitations of existing tapes in the regulation of peeling force and resistance value are solved, and higher adhesion and electrostatic protection are achieved, and the stability and safety of electronic equipment are protected.

CN119662143APending Publication Date: 2025-03-21SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411829682.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the field of electronic materials, existing single-sided tapes are difficult to meet the precise regulation of peeling force and surface resistance at the same time, resulting in insufficient adhesion performance or unsatisfactory electrostatic protection effect, and there is a potential risk to the stability and safety of electronic equipment.

Method used

By accurately controlling the ratio of crosslinking agent to antistatic agent in the adhesive layer, combined with the design of the antistatic coating, the performance of the single-sided tape can be optimized, so that it can flexibly adjust the peel force and resistance value.

Benefits of technology

The tape provides reliable adhesion and effective electrostatic protection in various environments, protecting electronic equipment from static damage, while improving production repeatability and market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662143A_ABST
    Figure CN119662143A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesive tapes, in particular to an anti-static adhesive tape for electronic materials and a preparation method of the anti-static adhesive tape. The prepared adhesive tape comprises a release film layer, an adhesive layer, an anti-static coating and a base material film layer from top to bottom. The anti-static coating is located between the base material film layer and the adhesive layer, and the base material film layer is bonded with the release film through the adhesive layer. Aiming at the special requirements of low adhesion and high anti-static performance of an electronic component on the protective film in the use process, accurate regulation and control of stripping force and surface resistance are realized by optimizing the ratio of a cross-linking agent to an anti-static agent in the adhesive layer; meanwhile, the problems that a traditional anti-static adhesive tape is too high in stripping force and sensitive elements are prone to being damaged are effectively solved, and the strict requirement of electronic materials for electrostatic protection is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive tapes, in particular to an antistatic adhesive tape for electronic materials and a preparation method thereof. Background Art

[0002] Single-sided tapes are widely used in the field of electronic materials, especially in scenarios where both fixation and anti-static functions are required, such as packaging and assembly of electronic components, and various protective coatings. However, existing single-sided tapes have certain limitations in performance regulation, especially in the matching of peel force and resistance value. Generally, it is impossible to achieve an accurate balance between the peel force and surface resistance value of traditional tapes, resulting in insufficient adhesion performance or unsatisfactory electrostatic protection effect in actual applications, which poses a potential risk to the stability and safety of electronic equipment.

[0003] The adhesive tape products currently on the market are usually optimized for a single performance, and it is difficult to simultaneously meet the precise control requirements of peeling force and surface resistance under different application conditions. For example, a single-sided ultra-thin adhesive tape disclosed in a Chinese patent with publication number CN205398535U includes a PET film layer, the upper surface of the PET film layer is covered with a primer layer, the upper surface of the primer layer is coated with a hot melt adhesive layer, the top end of the anti-scratch single-sided adhesive film is covered with a protective film layer, and an isolation adhesive layer is provided between the protective film layer and the hot melt adhesive layer. The anti-scratch single-sided adhesive film has a very high peelability, a very strong bonding force with the PET film, and good initial adhesion, and has an instantaneous high adhesion effect on the object being adhered.

[0004] However, high peel force may cause damage to the surface of sensitive components, while tape with low peel force may not provide sufficient adhesion. In addition, the PET film layer used in the tape has extremely high resistance, and the lack of electrostatic protection performance is more likely to cause failures during the production and use of electronic equipment. This limitation in performance optimization has become a technical problem that needs to be solved urgently in the field of electronic materials.

[0005] In order to solve the above problems, the present invention provides a method for optimizing the performance of a single-sided tape by precisely adjusting the ratio of a cross-linking agent to an antistatic agent in an adhesive layer. Summary of the invention

[0006] The object of the present invention is to provide an antistatic tape for electronic materials and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: an antistatic tape for electronic materials, comprising a release film layer, an adhesive layer, an antistatic coating layer and a substrate film layer in sequence, wherein the adhesive layer comprises, by weight:

[0008] 5-80 parts of acrylic glue; 0.1-10 parts of modified isocyanate crosslinking agent; 5-40 parts of ethyl acetate; 0.1-5 parts of imide salt antistatic agent;

[0009] The antistatic coating comprises, by weight, 1 to 10 parts of waterborne polyurethane, 0.1 to 1 part of modified isocyanate crosslinking agent, 0.2 to 3 parts of modified polythiophene antistatic agent, and 1 to 15 parts of normal hexane.

[0010] More optimally, the thickness of the release film layer is 20-75 μm.

[0011] More preferably, the thickness of the adhesive layer is 15 to 50 μm.

[0012] More optimally, the thickness of the antistatic coating is 0.2-1 μm.

[0013] More preferably, the substrate is one of polypropylene film, polyvinyl chloride film or polyester film.

[0014] More optimally, the 180° peel force of the tape is greater than 80gf / 25mm; the surface resistance is less than or equal to 3.2×10 8 Ω.

[0015] A method for preparing an antistatic tape for electronic materials, used for preparing any of the above antistatic tapes for electronic materials, comprises the following steps:

[0016] S1, taking 4 / 5 of the formula amount of ethyl acetate and mixing with acrylic glue, so that the acrylic glue is evenly dispersed in the solvent to obtain a dispersion;

[0017] S2, taking a certain amount of antistatic agent, adding it to the dispersion, and mixing it thoroughly to obtain dispersion B;

[0018] S3, dispersing and diluting the cross-linking agent with the remaining 1 / 5 of ethyl acetate, and adding the mixture into the dispersion B, further dispersing the mixture evenly to obtain a mixture;

[0019] S4, coating the obtained mixture on the antistatic surface of the substrate by means of a scraper, and drying at 110-130° C. to obtain a semi-finished product;

[0020] S5, laminating the semi-finished product with a release film, and placing the sample in an oven for curing to obtain a finished tape.

[0021] More optimally, in step S4, the coating speed is 20-30 m / min.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] (1) In the present invention, by finely adjusting the key ingredients in the formula, the peeling force of the tape can be flexibly adjusted, and its resistance value can be accurately controlled according to the requirements of different application scenarios. This technological innovation enables the single-sided tape to not only provide reliable adhesion in various environments, but also effectively prevent static electricity accumulation, thereby protecting electronic devices from static electricity damage.

[0024] (2) In the present invention, the antistatic tape is composed of a release film layer, an adhesive layer, an antistatic coating and a substrate film layer, wherein the antistatic coating is located between the substrate film layer and the adhesive layer. This design significantly reduces the resistance of the PET substrate surface by setting up an antistatic coating between the substrate film and the adhesive layer, avoids the accumulation of static electricity, and thus reduces the potential harm of static electricity to electronic components. In addition, the antistatic coating not only improves the antistatic performance of the tape, but also provides a larger design space for the formulation regulation of the adhesive layer. Through this structural optimization, the antistatic performance of the tape in different applications can be more accurately controlled, especially in the protection and packaging of electronic equipment that is sensitive to static electricity, showing better reliability.

[0025] (3) In the present invention, the adhesive layer adopts acrylic glue with moderate viscosity, and its excellent adhesion performance ensures that the tape can be stably adhered to a variety of substrates. By finely controlling the proportion of the cross-linking agent, the peeling force of the adhesive layer can be flexibly adjusted to adapt to different application requirements and ensure that the tape is not easy to damage the substrate or cause other adverse effects when peeling. At the same time, an antistatic agent is added to the adhesive layer to solve the resistance problem that may exist in the adhesive layer itself, and effectively enhance the antistatic performance of the tape. The addition of the antistatic agent not only helps to reduce static electricity accumulation, but also can adjust the amount of the antistatic agent added so that the resistance value of the adhesive surface can be accurately controlled according to different usage scenarios to meet different performance requirements from low resistance to high resistance. This flexible resistance value control capability enables the tape of the present invention to work stably in various environments, whether in high humidity, low temperature, or in industrial applications that require strict control of static electricity accumulation, it can provide reliable performance.

[0026] (4) In the present invention, by precisely controlling the ratio of the antistatic agent to the cross-linking agent, multiple optimizations of the adhesive tape in terms of adhesion and resistance are achieved, so that its performance can remain consistent under different application environments. In particular, in the packaging, assembly and protection of electronic components, the antistatic tape can effectively prevent damage to sensitive components caused by electrostatic discharge, while providing strong adhesion to ensure the stability and reliability of the tape during transportation and use. In addition, the adhesive tape product proposed by the present invention has high production process compatibility, can adapt to a variety of manufacturing processes, reduce variations in the production process, and improve production efficiency.

[0027] (5) In the present invention, the antistatic tape prepared has a wide range of applicability, not only suitable for the protection and packaging of electronic equipment and components, but also for the fixation and assembly of various electrostatic sensitive materials. Through the optimized formula of the present application, the tape can simultaneously meet the strict requirements of peeling force and resistance value, provide more precise performance control and higher production repeatability, and significantly improve the market competitiveness of the product and the expansibility of its application field. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 Schematic diagram of the structure of antistatic tape.

[0030] Among them, 1. release film layer; 2. adhesive layer; 3. antistatic coating; 4. release film layer. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention prepares several kinds of antistatic PET films and antistatic tapes, and detects their surface resistance and peeling force to verify the performance of the products of the present invention. The specific method is as follows:

[0033] Preparation example of antistatic PET film

[0034] Preparation Example 1

[0035] Step 1: Take 5 parts of waterborne polyurethane, 0.3 parts of isocyanate crosslinking agent, 0.2 parts of modified polythiophene antistatic agent, and 10 parts of n-hexane respectively, and mix them evenly in a high-speed mixer.

[0036] Step 2: The mixture in step 1 is coated on the surface of the substrate in a micro-dimpled manner and dried. The drying temperature is 110° C., the coating speed is 20 m / min, and the thickness is controlled at 0.3 μm.

[0037] Step 3: Roll up the sample in step 2 with the antistatic coating facing inward to obtain a finished product.

[0038] In addition, the above-mentioned preparation method was used to carry out Preparation Examples 2 to 7 in sequence; compared with Preparation Examples 1 to 2, the difference was that the addition amount of the antistatic agent and the electrostatic crosslinking agent and the thickness of the antistatic coating were different.

[0039] The specific amounts of antistatic agent and electrostatic crosslinking agent added in each preparation example and comparative preparation example are shown in Table 1.

[0040] Table 1. Table of the amount of antistatic agent and electrostatic crosslinking agent added in Preparation Examples 1 to 7 and Preparation Examples 1 to 2

[0041] sample Antistatic agent added amount (parts) Crosslinking agent (parts) Antistatic coating thickness (μm) Preparation Example 1 0.2 0.3 0.3 Preparation Example 2 0.4 0.3 0.3 Preparation Example 3 0.8 0.3 0.3 Preparation Example 4 1.5 0.3 0.3 Preparation Example 5 0.8 0.6 0.3 Preparation Example 6 1.5 0.6 0.3 Preparation Example 7 1.5 0.3 0.6 Comparative Preparation Example 1 0 0.3 0.3 Comparative Preparation Example 2 0 0.6 0.3

[0042] After the preparation was completed, the surface resistance of the antistatic PET films in Preparation Examples 1 to 7 and Preparation Examples 1 to 2 was measured, and the specific data are shown in Table 2.

[0043] Table 2 Surface resistance of antistatic PET film in Preparation Examples 1 to 7 and Preparation Examples 1 to 2

[0044]

[0045]

[0046] According to the test results in Table 2, it can be clearly observed that the amount of antistatic agent and electrostatic crosslinking agent added has a significant effect on the surface resistance of the antistatic PET film. By comparing the surface resistance of different embodiments, the key role of the antistatic agent in regulating the surface resistance is further verified.

[0047] In Preparation Examples 1 to 4, as the amount of antistatic agent added increases, the surface resistance decreases significantly. The surface resistances of Preparation Example 1 (the amount of antistatic agent added is 0.2 parts) and Preparation Example 2 (the amount of antistatic agent added is 0.4 parts) are 7.4×10 9 Ω and 6.5×10 8 Ω, compared with the PET substrate and the comparative preparation examples 1-2 without adding antistatic agent, the surface resistance exceeded the range, indicating that the coating without antistatic agent could not effectively reduce the surface resistance. It proves the importance of setting an antistatic layer to control the surface resistance of the tape.

[0048] As the amount of antistatic agent added further increased, the surface resistance of Preparation Example 3 (the amount of antistatic agent added was 0.8 parts) decreased to 9.4×10 7 Ω, the surface resistance of Preparation Example 4 (the amount of antistatic agent added was 1.5 parts) was reduced to 1.7×10 7 This result clearly shows that the amount of antistatic agent added is significantly negatively correlated with the surface resistance. With the increase of antistatic agent, the surface resistance of PET substrate decreases rapidly, showing a stronger antistatic effect.

[0049] In Preparation Examples 5 and 6, the amount of crosslinking agent added was increased to 0.6 parts, but the change in surface resistance was not significant, which was 9.4×10 7 Ω and 1.6×10 7 Ω. Compared with Preparation Example 3 and Preparation Example 4, the surface resistance has not been significantly improved, which indicates that the electrostatic crosslinking agent has little effect on the surface resistance, and its main effect may be concentrated on the crosslinking performance of the adhesive layer, rather than directly affecting the antistatic effect. Therefore, the amount of antistatic agent added is the main factor controlling the surface resistance, and the change of the crosslinking agent has a relatively limited effect on the resistance value.

[0050] In Preparation Examples 4 and 7, the thickness of the antistatic coating increased from 0.3 μm to 0.6 μm, and the surface resistance of PET changed significantly from 1.7×10 7 Ω is reduced to 6.8×10 6 Ω, the thickness of the surface coating has a greater influence on the surface resistance. By further increasing the coating thickness, the surface resistance of PET can be continuously reduced, thereby improving its antistatic performance.

[0051] The surface resistance of the PET substrate itself exceeds the range, indicating that the PET substrate has a higher surface resistance. By adding an antistatic coating on the PET surface and rationally controlling the addition amount of the antistatic agent, the surface resistance can be effectively reduced and its antistatic function can be enhanced. Especially in Preparation Example 3 (0.8 parts of antistatic agent) and Preparation Example 4 (1.5 parts of antistatic agent), the significant decline in surface resistance further proves the control ability of the antistatic agent to resistance.

[0052] Based on the test results of the surface resistance of the above preparation example, in order to explore the effect of the presence of the antistatic layer on the adhesive surface resistance and peeling force, an adhesive layer was further coated on the antistatic surface of the substrate to prepare an adhesive tape. The preparation method is as follows:

[0053] Step 1: Take 15 parts of acrylic glue and 5 parts of ethyl acetate and mix them evenly to make the acrylic glue evenly dispersed in the solvent to obtain a dispersion;

[0054] Step 2: Take one part of ethyl acetate to disperse and dilute 0.1 part of isocyanate crosslinking agent and add it to the dispersion, and further disperse it evenly to obtain a mixture;

[0055] Step 3: Apply the above mixture on the antistatic surface of the substrate by using a scraper, and dry at 110° C. for 2 minutes.

[0056] Step 4: The semi-finished product is then laminated with a release film, and the sample is placed in a 50° C. oven for aging for 48 hours to obtain a finished tape.

[0057] The above-mentioned preparation method was used to sequentially apply adhesive to Preparation Example 1, Preparation Example 4, Preparation Example 7 and Comparative Preparation Example 1 and compound them into finished tape products.

[0058] The surface resistance and 180° peeling force of the finished tape were tested, and the test data are shown in Table 3.

[0059] Table 3 Surface resistance and peeling force of each preparation example and comparative preparation example in this application

[0060] Sample number Surface resistance(Ω) 180° peeling force (gf / 25mm) Preparation Example 1 <![CDATA[4.9×10 11 ]]> 96.52 Preparation Example 4 <![CDATA[8.6×10 10 ]]> 96.69 Preparation Example 7 <![CDATA[2.6×10 9 ]]> 91.24 Comparative Preparation Example 1 Out of range 95.27

[0061] As can be seen from the results of Table 3, after applying adhesive on antistatic PET, the surface resistance of the sample has changed significantly. Using the adhesive tape of Preparation Example 1, Preparation Example 4 and Preparation Example 7, its surface resistance significantly increases after applying the adhesive layer than before applying, indicating that the resistance of the adhesive surface is much higher than the resistance of the antistatic layer, and the charge migration is mainly concentrated on the adhesive surface, resulting in the overall surface resistance being improved. This phenomenon shows that the resistance characteristics of the adhesive layer have an important influence on the final resistance value, especially when the resistance of the antistatic layer is relatively low, the resistance of the adhesive layer is particularly prominent. However, although the resistance of the adhesive layer has a large impact on the overall resistance value, when the resistance of the antistatic layer is sufficiently low, the resistance of the adhesive layer can be suppressed, thereby resulting in a significant reduction in the overall surface resistance. This verifies the effectiveness of the antistatic layer, that is, the antistatic coating can significantly improve the resistance characteristics, especially when the resistance of the antistatic layer is relatively low, the impact of the resistance of the adhesive layer on the overall resistance is effectively weakened.

[0062] Meanwhile, the peeling force results of Preparation Example 1 and Comparative Preparation Example 1 show that the thickness of the antistatic coating has a certain influence on the peeling force. Specifically, when the antistatic coating is thinner (such as Preparation Example 1), there is almost no influence on the peeling force of the adhesive tape. However, when the antistatic coating is too thick (such as Preparation Example 7), the peeling force decreases, indicating that the thicker antistatic layer can inhibit the adhesion of the adhesive tape.

[0063] Preparation example of antistatic tape

[0064] Based on the surface resistance test results of the antistatic PET film, Preparation Example 4 was selected as the substrate for subsequent experiments. The surface resistance of the PET has been reduced to 10 7 Ω, which is in line with the resistance range of general antistatic materials (10 6 ~10 10 Ω). Since the surface resistance will increase after the adhesive is applied, choosing a substrate with lower resistance as the bottom material can leave enough margin for the resistance change after the adhesive coating to ensure the effectiveness of the antistatic performance. The specific implementation is as follows:

[0065] Example 1

[0066] Step 1: Take 15 parts of acrylic glue and 5 parts of solvent and mix them evenly to make the acrylic glue evenly dispersed in the solvent;

[0067] Step 2: Add 0.2 parts of antistatic agent to the dispersion obtained in step 1 and mix thoroughly and evenly;

[0068] Step 3: Take one portion of solvent to disperse and dilute 0.1 portion of the cross-linking agent and add it to the dispersion obtained in step 2 to further disperse it evenly;

[0069] Step 4: Apply the mixture in step 3 onto the antistatic surface of the specific substrate by means of a spatula, and dry at 110° C. for 2 minutes.

[0070] Step 5: The semi-finished product is then laminated with a release film, and the sample is placed in a 50° C. oven for aging for 48 hours.

[0071] Using the above method, Examples 2 to 8 and Comparative Example 1 were implemented in sequence, the difference being that the amount of antistatic agent and crosslinking agent added was different. The specific amount of antistatic agent and crosslinking agent added in each Example and Comparative Example is shown in Table 4.

[0072] Table 4 Antistatic agent and crosslinking agent addition amount table of each embodiment and comparative example

[0073] sample Antistatic agent (parts) Crosslinking agent (parts) Example 1 0.2 0.1 Example 2 0.4 0.1 Example 3 0.6 0.1 Example 4 1.0 0.1 Example 5 1.0 0.3 Example 6 1.0 0.6 Example 7 1.0 1.0 Example 8 1.0 2.0 Comparative Example 1 0 0.1

[0074] After preparation, the surface resistance, 180° peeling force, and resistance and peeling force values ​​after being placed in an environment of 65°C / 90% for 168 hours were tested. The test data are shown in Table 5.

[0075] Table 5 Antistatic agent and crosslinking agent addition amount table of each embodiment and comparative example in this application

[0076]

[0077] Based on the data in Table 4 and Table 5, the present invention explores the effects of the content of antistatic agent and crosslinking agent in the adhesive layer on the antistatic performance, peeling force and aging performance, and the results are analyzed as follows:

[0078] 1. Surface resistance change:

[0079] As the amount of antistatic agent added increases (Examples 1 to 4), the initial surface resistance of the adhesive surface decreases significantly, for example, from 7.4×10 9 Ω is reduced to 3.2×10 8 Ω. This shows that the antistatic agent can effectively improve the conductivity of the rubber surface.

[0080] When the addition amount is further increased (Examples 5 to 8), the surface resistance tends to be stable and is maintained at about 3.1 to 3.3×10 8 This result shows that when the amount of antistatic agent added reaches a certain level, its effect on improving surface resistance is no longer significant.

[0081] The surface resistance of Comparative Example 1 is 8.6×10 10 , indicating that when no antistatic agent is added, the surface resistance of the adhesive surface has the risk of failing to achieve antistatic performance (10 6 ~10 10 Ω), so it is necessary to further add antistatic agent to the adhesive to meet the demand.

[0082] 2. Peel force changes

[0083] The initial peel force shows a downward trend as the amount of antistatic agent added increases, decreasing from 91.48 gf / 25 mm in Example 1 to 14.64 gf / 25 mm in Example 8.

[0084] Especially when the antistatic agent content is high (Examples 5 to 8), the peeling force decreases significantly. This is because excessive addition of the antistatic agent changes the molecular structure or interface properties of the adhesive, reducing the adhesion performance.

[0085] 3. Performance changes after aging

[0086] After aging for 168 hours at 65°C / 90%, the surface resistance of each sample increased slightly, but the overall change was small. For example, the resistance of Example 4 increased from 3.2×10 8 Ω increased to 3.7×10 8 Ω, indicating that the antistatic performance has good stability under high temperature and high humidity conditions.

[0087] The peel force generally decreases after aging, especially in the examples with high antistatic agent or high crosslinking agent content (such as Example 7 and Example 8), where the decrease is greater. This may be due to the further deterioration of the mechanical properties of the adhesive layer under aging conditions.

[0088] The experimental results fully show that by adjusting the amount of antistatic agent and crosslinking agent added, an optimal balance can be achieved between antistatic performance and peeling performance. In addition, the selection of antistatic PET with low surface resistance as the substrate provides a good basis for the regulation of the performance of the adhesive layer. This provides strong experimental support and data basis for the design and application of antistatic tapes.

[0089] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0090] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An antistatic tape for electronic materials, characterized in that: The invention comprises a release film layer, an adhesive layer, an antistatic coating layer and a substrate film layer in sequence, wherein the adhesive layer comprises, by weight: 5-80 parts of acrylic glue; 0.1-10 parts of modified isocyanate crosslinking agent; 5-40 parts of ethyl acetate; 0.1-5 parts of imide salt antistatic agent; The antistatic coating comprises, by weight, 1 to 10 parts of waterborne polyurethane, 0.1 to 1 part of modified isocyanate crosslinking agent, 0.2 to 3 parts of modified polythiophene antistatic agent, and 1 to 15 parts of normal hexane.

2. The antistatic tape for electronic materials according to claim 1, characterized in that: The release film layer has a thickness of 20 to 75 μm.

3. The antistatic tape for electronic materials according to claim 1, characterized in that: The thickness of the adhesive layer is 15 to 50 μm.

4. The antistatic tape for electronic materials and the preparation method thereof according to claim 1, characterized in that: The thickness of the antistatic coating is 0.5-3 μm.

5. The antistatic tape for electronic materials according to claim 1, characterized in that: The substrate is one of a polypropylene film, a polyvinyl chloride film or a polyester film.

6. The antistatic tape for electronic materials according to claim 1, characterized in that: The 180° peeling force of the tape is greater than 80gf / 25mm; the surface resistance is less than or equal to 3.2×10 8 Ω.

7. A method for preparing an antistatic tape for electronic materials, used for preparing any one of claims 1 to 6, characterized in that: The steps include: S1, taking 4 / 5 of the solvent in the formula and mixing it with the acrylic glue, so that the acrylic glue is evenly dispersed in the solvent to obtain a dispersion; S2, taking a certain amount of antistatic agent, adding it to the dispersion, and mixing it thoroughly to obtain dispersion B; S3, dispersing and diluting the cross-linking agent with the remaining 1 / 5 of the solvent, and adding the solvent into the dispersion B, further dispersing the cross-linking agent evenly to obtain a mixture; S4, coating the obtained mixture on the antistatic surface of the substrate by means of a scraper, and drying at 110-130° C. to obtain a semi-finished product; S5, laminating the semi-finished product with a release film, and placing the sample in an oven for curing to obtain a finished tape.

8. The method for preparing an antistatic tape for electronic materials according to claim 7, characterized in that: In the step S4, the coating speed is 20 to 30 m / min.

Citation Information

Patent Citations

  • Ultra -thin sticky tape of single face

    CN205398535U